Konten Dakwah Penceramah Perempuan: Analisis Respon Audien pada 'Suara Muslimah' di Kanal NU Online - Lukman Hakim; Agus Riyadi; Ali Murtadho (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2023)
This article aims to examine the audience's response to the da'wah content broadcasted by